Biofilms in chronic rhinosinusitis: Pathophysiology and therapeutic strategies. Issue 4 (1st December 2016) - Fastenberg, Judd H.; Hsueh, Wayne D.; Mustafa, Ali; Akbar, Nadeem A.; Abuzeid, Waleed M.
Abstract : Background: There is increasing evidence that biofilms are critical to the pathophysiology of chronic infections including chronic rhinosinusitis (CRS). Until relatively recently, our understanding of biofilms was limited. Recent advances in methods for biofilm identification and molecular biology have offered new insights into the role of biofilms in CRS. With these insights, investigators have begun to investigate novel therapeutic strategies that may disrupt or eradicate biofilms in CRS. Objective: This review seeks to explore the evidence implicating biofilms in CRS, discuss potential anti‐biofilm therapeutic strategies, and suggest future directions for research. Results: The existing evidence strongly supports the role of biofilms in the pathogenesis of CRS. Several anti‐biofilm therapies have been investigated for use in CRS and these are at variable stages of development. Generally, these strategies: 1) neutralize biofilm microbes; 2) disperse existing biofilms; or 3) disrupt quorum sensing. Several of the most promising anti‐biofilm therapeutic strategies are reviewed. Conclusions: A better understanding of biofilm function and their contribution to the CRS disease process will be pivotal to the development of novel treatments that may augment and, potentially, redefine the CRS treatment paradigm. There is tremendous potential for future research.